Acute T-cell lymphoblastic leukaemia presenting with cutaneous involvement in a child: a rare case report - Kalita, Lohit Kumar; Kalita, Chayanika; Gogoi, Pabitra Kumar; Sharma, Umesh Chandra (International Journal of Research in Medical Sciences, 2017)
Primary cutaneous involvement in T-cell lymphoblastic leukemia is rare in childhood. We present a case of 6-year-old girl admitted to our hospital because of multiple skin lesions. She was looked pale and weak. Generalized lymphadenopathy was present. Complete blood count revealed 216,000/mm3 white blood cell count. Peripheral blood smear showed 80% lymphoblasts. Bone marrow aspiration revealed 96% blastic cells with immunophenotype and morphological characteristics of acute lymphoblastic leukemia (T-ALL) which was confirmed by flowcytometry. ALL BFM -95 remission induction treatment protocol was started. Skin lesion remained same after two month of the cytotoxic therapy. The symptoms became more aggressive and she died after 4 months of treatment.